2012
DOI: 10.1021/ja209467h
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductive Liquid-Crystalline Derivatives of 6-Oxoverdazyl

Abstract: 1,3,5-Triphenyl-6-oxoverdazyl radicals 1[n], in which each phenyl group is substituted with three alkylsulfanyl groups (n = 6, 8, 10), exhibit a monotropic columnar rectangular (Col(r)) phase below 60 °C. Detailed analysis of 1[n] revealed a broad absorption band in the visible region with maxima at 540 and 610 nm and redox potentials E(1/2)(0/+1) = +0.99 V and E(1/2)(0/-1) = -0.45 V vs SCE. Photovoltaic studies of 1[8] demonstrated a hole mobility of 1.52 × 10⁻³ cm² V⁻¹ s⁻¹ in the mesophase with an activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…[11] Recently, we demonstrated that substituted triphenyl derivatives of verdazyl, a π-delocalised radical, form discotic hexagonal phases. [12][13][14] We have investigated three series of compounds containing 3,4,5-trialkoxyphenyl [12] (such as 1a), 3,4,5-trialkylsulfanylphenyl [13] and a mixture of both substituents. [14] The results demonstrated that the alkylsulfanyl derivatives form a disordered columnar hexagonal 3D phase (Col h(3D) ) below 60°C, presumably with a helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recently, we demonstrated that substituted triphenyl derivatives of verdazyl, a π-delocalised radical, form discotic hexagonal phases. [12][13][14] We have investigated three series of compounds containing 3,4,5-trialkoxyphenyl [12] (such as 1a), 3,4,5-trialkylsulfanylphenyl [13] and a mixture of both substituents. [14] The results demonstrated that the alkylsulfanyl derivatives form a disordered columnar hexagonal 3D phase (Col h(3D) ) below 60°C, presumably with a helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we reported that 1,3,5-tris(3,4,5-trialkylsulfanylphenyl)-6-oxoverdazyls (1a[n], n = 6, 8, and 10, Chart 1) form a monotropic columnar rectangular phase (Col r ) below 60 1C. 1 The compounds are dark blue due to a broad absorption band in the visible region (l max = 540 nm and 610 nm in hexane). Their redox potentials are E 0/+1 1/2 = +0.99 V and E 0/À1 1/2 = À0.45 V vs. SCE, and photovoltaic studies of 1a [8] revealed a hole mobility of m h E 1.5 Â 10 À3 cm 2 V À1 s À1 in the mesophase with an activation energy E a = 0.06 AE 0.01 eV.…”
mentioning
confidence: 99%
“…The measured potentials, E 0/+1 1/2 = +0.83 V and E 0/À1 1/2 = À0.60 V vs. SCE, are shifted cathodically by about 0.16 V relative to those reported for 1a [6]. 1 The observed cell potential E cell = 1.43 V is consistent with a relatively low disproportionation energy calculated for 1b [1] (rigid, 107.5 kcal mol À1 ; relaxed, 92.3 kcal mol À1 ).…”
mentioning
confidence: 99%
“…Such self-assembled aromatic onedimensional columns that combine metal-metal, p-p, and metal-p interactions favor charge transport along the column chains, favoring applications in organic electronics, for example, in organic photovoltaics (OPVs), light-emitting diodes (OLEDs), and field-effect transistors (OFETs). [14] One highlight of the stack is the aromatic (benzene) 2 p-dimer, which is sandwiched between cofacially stacked macrocycles 1 and enclosed by the fluorine-lined hydrophobic cavity formed by twelve fluorous n-C 3 F 7 groups. A single benzene molecule is also sandwiched between two cofacial PtOEP planes and is well-nested within a cavity formed by 16 ethyl groups (Scheme 1 c, iii).…”
mentioning
confidence: 99%